1996
DOI: 10.1021/ja9629975
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Evidence for Oxirane Formation Reaction of Pentacoordinate 1,2λ6-Oxathietanes with Retention of Configuration

Abstract: From our interest in diheteracyclobutanes 1 bearing highly coordinate main group elements at the neighboring position, 1,2 we have reported the synthesis and thermolysis of the pentacoordinate 1,2λ 6 -oxathietane 2. 3,4 Almost quantitative oxirane formation from 2 has suggested a possibility that the oxathietane is an intermediate of the Corey-Chaykovsky reaction of oxosulfonium ylides with carbonyl compounds. 3It has been proposed that the Corey-Chaykovsky reaction 5 involves the formation of an anti-betaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 13 publications
(16 reference statements)
0
31
0
Order By: Relevance
“…The preparation of Tol 2 SbCl from Tol 3 Sb (16) and SbCl 3 (7) was tried repeatedly according to procedures described for Ph 2 SbCl. [28] However, we found that a large amount of byproducts such as TolSbCl 2 and Tol 3 SbCl 2 were always formed, so we were not able to isolate Tol 2 SbCl in pure form by recrystallization, although various solvents were examined.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The preparation of Tol 2 SbCl from Tol 3 Sb (16) and SbCl 3 (7) was tried repeatedly according to procedures described for Ph 2 SbCl. [28] However, we found that a large amount of byproducts such as TolSbCl 2 and Tol 3 SbCl 2 were always formed, so we were not able to isolate Tol 2 SbCl in pure form by recrystallization, although various solvents were examined.…”
Section: Resultsmentioning
confidence: 99%
“…The symmetry-forbidden apical-equatorial-coupling process has been reported once to be favored, [8] whereas recent calculations support the conclusion by Hoffmann that equatorial-equatorial coupling is the lowest energy process for PH 5 , AsH 5 , and SbH 5 , [9][10][11][12] although BiH 5 favors the apical-equatorial process. [11] Experimentally, the LCR of bis(biphenylene)methylphosphorane, [13] tetraaryltellurium, [14] 2-pyridylsulfuranes (generated in situ), [15] pentavalent oxathietane, [16] and pentavalent oxastibetane [17] have been reported, however, the essential nature of the selectivity of the LCR has yet to be discussed. We have already reported on the LCR of triarylbis(phenylethynyl)antimony(V) compounds for this purpose and found that no biaryls were formed from the LCR (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Upon treatment of one equivalent of H2O2 with compound 36, a sharp peak was appeared at 863 ppm in the Se-NMR and mass spectral studies ( Figures S24-S27, SI). Sulfurane oxide and selenurane oxide with apical oxygen atoms are already known in the literature [17][18][19]. However, compound 38 is the first example of a stable selenurane oxide, which contains two nitrogen atoms at the axial positions.…”
Section: Mechanism Of Cyclizationmentioning
confidence: 99%
“…However, the corresponding aromatic derivatives 6-7 were found to be much less active than the aliphatic compounds 4-5 [15,16]. Several sulfurane oxides and selenurane oxides such as 8-10, in which the chalcogen atoms are in the higher oxidation state, were also synthesized and isolated ( Figure 1) [17][18][19]. Although several example of spirodioxyselenuranes are available in the literature, examples of stable spirodiazaselenuranes are very rare.…”
Section: Introductionmentioning
confidence: 99%
“…The other is ligand dissociation to form a sulfonium salt followed by a nucleophilic attack on another ligand by the dissociated ligand. Although the ligand-coupling mechanism is common in the chemistry of hypervalent organosulfur compounds [1], some reactions have been reported to proceed via the latter reaction mechanism [2]. We reported previously that the thermolysis of a 1,2λ 6 -oxathietane, a pentacoordi- nated sulfurane bearing the Martin ligand [3] and a four-membered ring, gave the oxirane with retention of the relative configuration, suggesting the ligandcoupling mechanism [2].…”
Section: Introductionmentioning
confidence: 97%